Interprofessional collaboration between different health care professions in Emilia Romagna - Carradore, Marco; Michelini, Enrica; Caretta, Ingrid; Carpi, Sara; Corradini, Luca; Ganapini, Silvia; Lumetta, Francesco; Paterlini, Giulia; Pedroni, Emily; Russo, Alessandra; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Background: Interprofessional collaboration in the healthcare sector contributes to the delivery of high quality and safe services to patients across different subdivisions of the healthcare system which is faced with constant challenges. The international literature offers a plethora of tools for assessing the collaboration between health workers, but only a few of these have been validated in the Italian language. One that has undergone such validation is the interprofessional collaboration (IPC) scale, which measures the perception of collaboration among health professionals. An advantage of this scale is that is addresses all workers within the system, and is not limited to specific professions. The aim of the present study was to apply the validated Italian version of the IPC scale, to a context different to the one used for its validation, to measure the level of collaboration between different health care workers. Method: A questionnaire-based study was conducted on a sample consisting of 329 health professionals working at Azienda USL-IRCCS in Reggio Emilia. The categorical and continuous variables were analysed using descriptive statistics (frequencies, percentages and SD). Results: The IPC scale showed physicians to express the highest level of collaboration with other professionals, in line with the results of other studies in the literature. The values calculated for the factors “accommodation” and “communication” were higher than for “isolation”, depicting a good level collaboration. The only case in which the isolation factor, which describes an absence of collaboration, was equal to the other two factors was in relation to the evaluation of midwives by nursing aides/orderlies. Conclusions: In conclusion, the Italian version of the IPC scale provides a useful instrument for measuring interprofessional collaboration between workers in the healthcare sector. In the present study, it revealed a satisfactory level of collaboration between health professionals in an organization located in Emilia Romagna, Italy.